2016
DOI: 10.3920/wmj2015.2004
|View full text |Cite
|
Sign up to set email alerts
|

Crops are a main driver for species diversity and the toxigenic potential ofFusarium isolates in maize ears in China

Abstract: In recent years increasing demands and the relatively low-care cultivation of the crop have resulted in an enormous expansion of the acreage of maize in China. However, particularly in China, Fusarium ear rot forms an important constraint to maize production. In this study, we showed that members of both the Fusarium fujikuroi species complex (FFSC) and the Fusarium graminearum species complex are the causal agents of Fusarium ear rot in the main maize producing areas in China. Fumonisin producing Fusarium ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 69 publications
(106 reference statements)
1
22
0
Order By: Relevance
“…In South Africa, F. boothii was shown to be the best colonizer and mycotoxin producer on maize whereas F. graminearum was predominant on wheat [ 17 , 18 ]. Similar results were found in China, where F. boothii was prominent when maize is cultivated without rotation with wheat or rice [ 19 ]. However, nearly all studies in different agroecosystems focus on the pathogenic stage of Fusarium and there are few reports on the saprophytic stage on crops residues, which is crucial to the lifecycle and epidemiology of the pathogen.…”
Section: Introductionsupporting
confidence: 84%
“…In South Africa, F. boothii was shown to be the best colonizer and mycotoxin producer on maize whereas F. graminearum was predominant on wheat [ 17 , 18 ]. Similar results were found in China, where F. boothii was prominent when maize is cultivated without rotation with wheat or rice [ 19 ]. However, nearly all studies in different agroecosystems focus on the pathogenic stage of Fusarium and there are few reports on the saprophytic stage on crops residues, which is crucial to the lifecycle and epidemiology of the pathogen.…”
Section: Introductionsupporting
confidence: 84%
“…It is well-known that F. graminearum is the most destructive pathogens of Fusarium head blight (FHB) [55,56] and maize ear and stalk rot in China and many other countries [51,52,57,58], while F. asiaticum was more frequently isolated with isolation frequency up to 60% than F. graminearum in Southwest China [56]. Fusarium meridionale is the predominant species on maize in Nepal and Northern Argentina [56] but at quite low frequency in other countries such as South Korea [59]. In our previous studies, F. meridionale was only rarely isolated from wheat and maize in Southwest China including Sichuan and its surrounding areas [56,57], but the factors which influence its distribution are still unknown.…”
Section: Pcr Amplification and Phylogenetic Analysismentioning
confidence: 99%
“…Fusarium graminearum is more frequently associated with maize and wheat rotation when F. asiaticum appear in rice and wheat rotation in Korea [61]. Similarly, multiple intercropping patterns such as rice and maize rotation, wheat/maize and maize/soybean intercropping are widely practiced in Sichuan Province of China [19], and this could put a selective stress on different hosts and help these species of FGSC to shift onto soybean from wheat or maize [56,59]. In addition, we observed that the disease incidence of root rot significantly increased in 2018 as compared to the previous years in two cropping patterns, which was followed by more rainfall days, especially mid of July 2018 during the soybean growth stage ( Figure S1).…”
Section: Pcr Amplification and Phylogenetic Analysismentioning
confidence: 99%
“…The symptoms of this disease are associated with affected internal stem tissue, characterized by brown streaks in the internodes at early stages and a pink discoloration in mature plants (Shin et al, 2014). Several Fusarium species, which include F. graminearum, F. temperatum, F. subglutinans, F. proliferatum and F. verticillioides, have been reported as associated with maize plants with symptoms of this disease (Shin et al, 2014;Gromadzka et al, 2016;Zhang et al, 2016;Gromadzka et al, 2018). Some of these fungal species can also produce mycotoxins and may be seed-transmitted, leading to significant yield losses and a decrease in seed quality (Leslie and Summerell, 2006).…”
Section: Introductionmentioning
confidence: 99%